Transforming Library Services in the Digital Age: A Literature Review on the Evolution, Challenges, and Future Directions of Digital Libraries - Utami, Batina Yulia; Elmanisar, Velnika; Rusdinal, Rusdinal; Anisah, Anisah; Setiawati, Merika (International Journal of Educational Dynamics, 2024)
This literature review explores the historical development, current challenges, and future directions of digital library services, with a focus on how Information and Communication Technology (ICT) has reshaped library management, enhanced user engagement, and facilitated the transition from traditional to digital systems. Using a library study methodology, the study systematically analyzes secondary data, including books, journal articles, and reports, to synthesize insights into the evolution of digital libraries. Key findings highlight the transformative impact of ICT, which has broadened the scope of library services, enabling the management of digital collections and enhancing accessibility through local networks and online platforms. Additionally, the study examines the role of digital librarians, whose expertise in technology and user behavior is critical to the success of digital libraries. The review concludes that libraries must continuously innovate, foster collaboration, and invest in professional development to sustain their relevance in the digital era. These findings contribute to identifying best practices and innovations for advancing library services in an increasingly digital and information-driven society.